Anti-inflammatory effects of a traditional Korean medicine: Ojayeonjonghwan - Sun-Young Nam; Kyu-Yeob Kim; Mi Hye Kim; Jae-Bum Jang; So-Young Rah; Jin-Man Lee; Hyung-Min Kim; Hyun-Ja Jeong (Taylor & Francis Group, 2017)
Objective: To study the anti-inflammatory properties of OJ. Context: Ojayeonjonghwan (OJ) is a traditional Korean prescription, which has been widely used for the treatment of prostatitis. However, no scientific study has been performed of the anti-inflammatory effects of OJ. Materials and methods: Peritoneal macrophages were isolated 3-4 days after injecting a C57BL/6J mouse with thioglycollate. They were then treated with OJ water extract (0.01, 0.1, and 1 mg/mL) for 1 h and stimulated with lipopolysaccharide (LPS) for different times. Nitric oxide (NO), inducible nitric oxide synthase (iNOS) and cyclooxygenase (COX)-2, and proinflammatory cytokine levels were determined by NO assay, Western blotting, RT-PCR and ELISA. Results: NO generation and iNOS induction were increased in the LPS-activated mouse peritoneal macrophages. However, NO generation and iNOS induction by LPS were suppressed by treatment with OJ for the first time. The IC50 value of OJ with respect to NO production was 0.09 mg/mL. OJ did not influence LPS-stimulated COX-2 induction, but did significantly decrease LPS-stimulated secretions and mRNA expressions of tumour necrosis factor (TNF)-α, interleukin (IL)-6, and IL-1β. Inhibition rates of TNF-α, IL-6, and IL-1β at an OJ concentration of 1 mg/mL were 77%, 88%, and 50%, respectively. OJ also suppressed the LPS-induced nuclear translocation of NF-κB. High-performance liquid chromatography showed schizandrin and gomisin A are major components of OJ. Conclusions: OJ reduces inflammatory response, and this probably explains its positive impact on the prostatitis associated inflammation.